An approach to spectral analysis of psychologically influenced speech - Jena, Bhagyalaxmi; Sekhar Singh, Sudhansu (International Journal of Engineering and Technology, 2017)
The significant part of any speech signal lies in the information content and the emotions contents like stress or fatigue at a particular period of time. The classification of various types of stress and their effects are defined here. To analyze the changes in stressed speech than that of the normal speech, a database has been created which has investigated the stress among students during the examination in our college. In this paper, the spectral analysis of speech is done where emphasis has been given in the parameters like Fast Fourier Transform (FFT), spectrogram and Power Spectral Density (PSD). These parameters have been simulated using MATLAB codes. The comparison of the mentioned parameters is also done between a normal speech and a psychological stressed speech.
Keywords: Speech Signal; Stress; Fast Fourier Transform; Spectrogram; Power Spectral Density.